Juridical Analysis of the Handling of Domestic Violence by LPPA in Banyumas City - Enggar Asep Fitrianto (UM Purwokerto Press, 2023)
Domestic violence is a serious problem that harms individuals, families and society at large. To overcome the negative impacts caused, the government and non-governmental organizations have established institutions in charge of handling domestic violence cases. One of the institutions responsible for this is the Institute for the Protection of Women and Children (LPPA) of Banyumas City. This study aims to examine and understand more deeply the role of LPPA institutions in Banyumas city and to examine and how the effectiveness of legal protection carried out against victims of domestic violence. The method used is normative juridical research with a statutory approach. The data used is sourced from laws, relevant legislation, as well as policies and guidelines implemented by LPPA in Banyumas city.